Measurements of Weight Bearing Asymmetry Using the Nintendo Wii Fit Balance Board Are Not Reliable for Older Adults and Individuals With Stroke - Liuzzo, Derek M. (J Geriatr Phys Ther, 2017)
BACKGROUND: Clinicians and researchers have used bathroom scales, balance performance monitors with feedback, postural scale analysis, and force platforms to evaluate weight bearing asymmetry (WBA). Now video game consoles offer a novel alternative for assessing this construct. By using specialized software, the Nintendo Wii Fit balance board can provide reliable measurements of WBA in healthy, young adults. However, reliability of measurements obtained using only the factory settings to assess WBA in older adults and individuals with stroke has not been established. PURPOSE: To determine whether measurements of WBA obtained using the Nintendo Wii Fit balance board and default settings are reliable in older adults and individuals with stroke. METHODS: Weight bearing asymmetry was assessed using the Nintendo Wii Fit balance board in 2 groups of participants—individuals older than 65 years (n = 41) and individuals with stroke (n = 41). Participants were given a standardized set of instructions and were not provided auditory or visual feedback. Two trials were performed. Intraclass correlation coefficients (ICC), standard error of measure (SEM), and minimal detectable change (MDC) scores were determined for each group. RESULTS: The ICC for the older adults sample was 0.59 (0.35–0.76) with SEM(95)= 6.2% and MDC(95)= 8.8%. The ICC for the sample including individuals with stroke was 0.60 (0.47–0.70) with SEM(95)= 9.6% and MDC(95)= 13.6%. DISCUSSION: Although measurements of WBA obtained using the Nintendo Wii Fit balance board, and its default factory settings, demonstrate moderate reliability in older adults and individuals with stroke, the relatively high associated SEM and MDC values substantially reduce the clinical utility of the Nintendo Wii Fit balance board as an assessment tool for WBA. CONCLUSIONS: Weight bearing asymmetry cannot be measured reliably in older adults and individuals with stroke using the Nintendo Wii Fit balance board without the use of specialized software.